Negative electrode material for secondary battery
A silicon-based negative electrode material with residual compressive stress and specific peak ratios enhances mechanical and electrochemical stability, addressing insulation and volume change issues, achieving high discharge capacity and retention rates.
Patent Information
- Application Number
- JP2024536054
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-14
- Filing Date
- 2022-11-17
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2042-11-17
AI Technical Summary
Conventional silicon-based negative electrode materials for secondary batteries suffer from rapid deterioration due to insulation issues caused by large volume changes, particle detachment, and irreversible lithium loss, leading to poor initial charge/discharge efficiency and cycle characteristics, making them difficult to commercialize.
A negative electrode material composed of silicon oxide and a doping element, such as alkali or alkaline earth metals, with silicon nanoparticles dispersed in a matrix, exhibiting residual compressive stress, and specific peak ratios and properties in X-ray diffraction and Raman spectra, ensuring improved mechanical and electrochemical stability.
The material achieves high discharge capacity and capacity retention rates, overcoming the limitations of conventional silicon-based electrodes by maintaining structural integrity and electrochemical performance, enabling practical commercialization.
Smart Images

Figure 2024546974000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anode material for a secondary battery, and more particularly to an anode material for a secondary battery having improved capacity, initial efficiency, and cycle characteristics. [Background technology]
[0002] In various industrial fields such as electronic products, electric / hybrid vehicles, and aerospace / drones, the demand for secondary batteries that not only have high energy density and high power density characteristics but also can be used for a long period of time, i.e., have a long life span, continues to increase.
[0003] Generally, a rechargeable secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. Among them, a representative negative electrode material that is commercially used is graphite, but the theoretical maximum capacity of graphite is only 372 mAh / g.
[0004] Therefore, in order to realize secondary batteries with high energy density, ongoing research is being conducted into the use of chalcogen-based materials such as sulfur (maximum capacity 1,675 mAh / g), silicon-based materials such as silicon (maximum capacity 4,200 mAh / g) and silicon oxide (maximum capacity 1,500 mAh / g), and transition metal oxides as negative electrode materials for secondary batteries, and among the various materials, silicon-based negative electrode materials are attracting the most attention.
[0005] However, when particulate silicon is used as the anode material, as charge-discharge cycling is repeated, the battery characteristics rapidly deteriorate due to insulation caused by large volume changes in silicon, particle detachment, increased contact resistance, etc., and the battery loses its function within 100 cycles. In the case of silicon oxide, there is a problem that lithium is lost due to irreversible products such as lithium silicate and lithium oxide, and the initial charge-discharge efficiency rapidly decreases.
[0006] In order to solve these problems of silicon-based anode materials, a technology has been proposed in which silicon is nano-sized in the form of wires or the like and then composited with carbon materials, a technology in which silicon oxide is doped with a different metal to form a composite oxide phase, or a technology in which silicon oxide is pre-lithiated. However, these technologies are still inferior in initial charge / discharge efficiency, cycle characteristics, high-rate characteristics, etc., making commercialization difficult. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 10-2020-0065514 [Patent Document 2] Korean Patent Publication No. 10-2015-0045336 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a negative electrode material for a silicon-based secondary battery having high battery capacity, improved initial reversible efficiency and stable cycle characteristics. [Means for solving the problem]
[0009] The negative electrode material for a secondary battery according to one embodiment of the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of one or more of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix. The negative electrode material for a secondary battery according to one embodiment of the present invention includes a half cell having a counter electrode made of a metallic lithium foil. During a charge-discharge test under the following charge-discharge cycle conditions, the following formula 1 is satisfied, and the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of a second peak (A2) located in the range of 28±0.5° satisfies 0.8 to 6.
[0010] Charge / discharge cycle conditions: constant current / constant voltage (CC / CV), cut-off voltage 0.005V~1.0V, 0.5 charge / discharge rate (C-rate)
[0011] (Formula 1) 95%≦C50 / C1*100
[0012] In Equation 1, C1 is the discharge capacity (mAh / g) at the first charge / discharge cycle, and C50 is the discharge capacity at the 50th charge / discharge cycle.
[0013] In the negative electrode material for secondary batteries according to one embodiment of the present invention, the ratio (L1 / L2) of the full width at half maximum (FWHM(L1)) of a first peak located in a diffraction angle 2θ range of 10° to 27.4° in an X-ray diffraction pattern using CuKα radiation to the full width at half maximum (FWHM(L2)) of a second peak located in a diffraction angle 2θ range of 28±0.5° can be 6 to 15.
[0014] In the negative electrode material for secondary batteries according to an embodiment of the present invention, the intensity ratio (I1 / I2) between the maximum intensity of the first peak (I1) and the maximum intensity of the second peak (I2) may be 0.05 to 1.25.
[0015] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the first peak may be derived from an amorphous silicon oxide, and the second peak may be derived from a crystalline silicon.
[0016] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the discharge capacity C50 at the 50th charge-discharge cycle may be 1150 mAh / g or more.
[0017] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the Raman peak full width at half maximum (FWHM) of the nanoparticle silicon contained in the negative electrode material may be greater than the Raman peak full width at half maximum (FWHM) of bulk single crystal silicon.
[0018] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the half width (FWHM) of the Raman peak of the nanoparticle-shaped silicon contained in the negative electrode material is 4 to 20 cm. -1 It can be.
[0019] In the negative electrode material for secondary batteries according to an embodiment of the present invention, the following formula 2 can be satisfied based on the Raman signal of silicon.
[0020] (Formula 2) 1 <WN(Si) / WN(ref)
[0021] In Equation 2, WN(ref) is the central wavenumber of the Raman peak of bulk single crystal silicon, and WN(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material.
[0022] In the negative electrode material for a secondary battery according to an embodiment of the present invention, when a two-dimensional mapping analysis is performed based on the Raman signal of silicon, the difference between the maximum and minimum shifts defined by the following formula 3 under the following mapping conditions is 5 cm -1 It can be the following:
[0023] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 , mapping size = 14 μm × 14 μm
[0024] (Formula 3) deviation=WN i (Si)-WN(ref)
[0025] In Equation 3, WN(ref) is the same as in Equation 2, and WN i (Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material in one pixel, which is the unit analysis area during mapping analysis.
[0026] In the negative electrode material for secondary batteries according to an embodiment of the present invention, when a shift analysis is performed based on the Raman signal of silicon at 20 different random positions on a 20 mm x 20 mm test piece, the difference between the maximum and minimum shifts defined by the following formula 3 is 5 cm -1 It can be the following:
[0027] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1
[0028] (Formula 3) deviation=WN i (Si)-WN(ref)
[0029] In Equation 3, WN(ref) is the same as in Equation 2, and WN i (Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material in one pixel, which is the unit analysis area during mapping analysis.
[0030] In the negative electrode material for a secondary battery according to an embodiment of the present invention, a compressive stress may be 80% or more when stress analysis is performed on silicon nanoparticles at 20 different random positions on a 20 mm×20 mm test piece.
[0031] The negative electrode material for a secondary battery according to an embodiment of the present invention may include a plurality of negative electrode material particles and have a composition uniformity among the particles according to the following formula 4:
[0032] (Formula 4) 1.3≦UF(D)
[0033] In formula 4, UF(D) is a value obtained by dividing the average doping element composition among the negative electrode material particles by the standard deviation of the doping element composition based on the weight percent composition.
[0034] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the silicon nanoparticles may have an average diameter of 2 to 30 nm.
[0035] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the interface between the silicon nanoparticles and the matrix may be a coherent interface.
[0036] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the doping element is lithium ( Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi).
[0037] In one embodiment of the present invention, the negative electrode material for a secondary battery has an average diameter of 10 0 μm order ~ 10 1 It may be in the form of particles on the order of μm.
[0038] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the negative electrode material may further include a coating layer containing carbon.
[0039] The present invention includes a secondary battery including the above-mentioned negative electrode material for a secondary battery. Effect of the Invention
[0040] The negative electrode material for secondary batteries according to the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of at least one of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and contained in the matrix. During a charge-discharge test under specific charge-discharge cycle conditions using a half cell having a counter electrode made of a metal lithium foil, the negative electrode material satisfies the formula 95%≦C50 / C1*100, and has the advantages of having excellent discharge capacity and a capacity retention rate at a level that allows for practical commercialization of secondary batteries equipped with the silicon-based negative electrode material, as well as improved mechanical and electrochemical properties due to crystallographic properties based on an X-ray diffraction pattern. [Brief description of the drawings]
[0041] [Figure 1] FIG. 2 is a diagram showing an EDS line profile of magnesium (Mg) measured by Energy Dispersive X-ray Spectroscopy (EDS) in a cross section of a negative electrode material manufactured according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing an X-ray diffraction (XRD) pattern of a negative electrode material manufactured according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a graph showing Raman spectra of a negative electrode material prepared according to an embodiment of the present invention. [Figure 4] FIG. 2 is a diagram showing a two-dimensional mapping result based on the Raman signal of silicon of an anode material manufactured according to an embodiment of the present invention. [Diagram 5] FIG. 4 is a diagram showing the results of measuring the strength and elastic modulus of a negative electrode material manufactured according to an embodiment of the present invention. [Figure 6] 4A and 4B are graphs showing the charge / discharge capacity and capacity retention rate of a half cell having a negative electrode including a negative electrode material prepared according to an embodiment of the present invention, according to the charge / discharge cycles. [Figure 7]4(a) and 4(b) are dQ / dV graphs of half cells provided with negative electrodes containing the negative electrode materials produced in Examples 1 to 3 and Comparative Examples 1 to 3, respectively. [Figure 8] 1 is a high-magnification transmission electron microscope photograph of a negative electrode material manufactured according to an embodiment of the present invention; [Figure 9] 4 is a scanning electron microscope photograph showing a cross section and thickness of a negative electrode including a negative electrode material manufactured according to an embodiment of the present invention before lithiation and a cross section and thickness of a negative electrode after lithiation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] The negative electrode material for secondary batteries of the present invention will be described in detail below with reference to the accompanying drawings. The drawings presented herein are provided as examples to fully convey the concept of the present invention to those skilled in the art. Therefore, the present invention is not limited to the drawings presented below, and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. In this case, unless otherwise defined, the technical and scientific terms used have the meanings that are commonly understood by those having ordinary knowledge in the technical field to which the present invention belongs, and descriptions of known functions and configurations that may unnecessarily obscure the gist of the present invention in the following description and the accompanying drawings are omitted.
[0043] Also, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0044] In this specification and the appended claims, the terms "first," "second," and the like are not used in a limiting sense but are used to distinguish one element from another element.
[0045] In this specification and the appended claims, the terms "comprise" or "have" mean the presence of the features or components described in the specification, and do not preclude the possibility that one or more other features or components may be added, unless specifically limited.
[0046] In this specification and the appended claims, when a part such as a film (layer), region, or component is said to be on or above another part, it includes not only the case where it is directly on top of the other part in contact with it, but also the case where another film (layer), other region, other component, etc. is interposed between them.
[0047] The applicant found that in a silicon-based negative electrode material in which silicon and a silicon-based oxide are composited, the mechanical properties and electrochemical properties of the negative electrode material are significantly affected by the residual stress of the silicon contained in the negative electrode material. As a result of further research based on this knowledge, the applicant found that when silicon is dispersed in the form of nanoparticles in a matrix based on a silicon-based oxide and has a residual compressive stress, the mechanical properties and electrochemical properties of the negative electrode material are significantly improved, and thus the present invention was completed.
[0048] Therefore, the negative electrode material of the present invention based on the above-mentioned findings exhibits mechanical properties and electrochemical properties that could not be obtained from conventional silicon-based negative electrode materials due to the bond between silicon dispersed in nanoparticle form and having residual compressive stress and the matrix, and the present invention includes various aspects based on the properties of the silicon-based negative electrode material of the present invention.
[0049] The matrix in the present invention may refer to a solid phase medium in which nanoparticle silicon is dispersed, and may refer to a material that forms a continuous phase compared to silicon nanoparticles that are a dispersed phase in the negative electrode material. The matrix in the present invention may refer to a material other than metallic silicon (Si) in the negative electrode material.
[0050] In the present invention, nanoparticles are generally defined as having a size (diameter) of 100 Nanometer order ~ 10 2 Nanometer-order particles can refer to particles having a diameter substantially less than 500 nm, specifically less than 200 nm, more specifically less than 100 nm, and even more specifically less than 50 nm.
[0051] In the present invention, the negative electrode material for a secondary battery includes, but is not necessarily limited to, a negative electrode material for a lithium secondary battery. The negative electrode material of the present invention can be used as an active material for secondary batteries such as sodium batteries, aluminum batteries, magnesium batteries, calcium batteries, and zinc batteries, and can be used in supercapacitors, dye-sensitized solar cells, fuel cells, and the like, in place of conventional silicon-based materials. The technology can also be used in other energy storage / generation devices where
[0052] The negative electrode material for secondary batteries according to one embodiment (I) of the present invention comprises: a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of at least one of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix; and during a charge-discharge test under the following charge-discharge cycle conditions using a half cell in which a counter electrode is a metallic lithium foil, the negative electrode material satisfies formula 1, and the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° and the area of a second peak (A2) located in the range of 28±0.5° in an X-ray diffraction pattern using CuKα radiation is 0.8 to 6.
[0053] Charge / discharge cycle conditions: constant current / constant voltage (CC / CV), cut-off voltage 0.005V~1.0V, 0.5 charge / discharge rate (C-rate)
[0054] (Formula 1) 95%≦C50 / C1*100
[0055] In formula 1, C1 is the discharge capacity (mAh / g) of the negative electrode material in the first charge / discharge cycle, and C50 is the discharge capacity of the negative electrode material in the 50th charge / discharge cycle. In this case, C1 in the first charge / discharge cycle may be the discharge capacity of the negative electrode material measured after the chemical formation process is performed once and / or twice.
[0056] Specifically, Equation 1 is an index showing a capacity retention rate during 50 charge / discharge cycles. The negative electrode material for a secondary battery according to the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of at least one of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and contained in the matrix. During a charge / discharge test under specific charge / discharge cycle conditions using a half cell in which a counter electrode is a metallic lithium foil, the negative electrode material has a capacity retention rate of 95% or more. In an X-ray diffraction pattern using CuKα rays, the ratio (A1 / A2) between the area of a first peak (A1) located in a range of a diffraction angle 2θ of 10° to 27.4° and the area of a second peak (A2) located in a range of 28±0.5° satisfies 0.8 to 6, thereby enabling the secondary battery including the silicon-based negative electrode material to have improved mechanical properties and electrochemical properties as well as a capacity retention rate at a level that enables practical commercialization.
[0057] Hereinafter, unless otherwise specified, the electrochemical characteristics of the negative electrode material including the charge / discharge characteristics (discharge capacity, volume change during lithiation, dQ / dV graph, etc.) may be the electrochemical characteristics of a half cell in which the negative electrode containing the negative electrode material and the counter electrode are metallic lithium foil, and may be the electrochemical characteristics of a half cell in which a formation process has been performed. Therefore, it goes without saying that the first cycle according to the charge / discharge cycle conditions in the charge / discharge test also means the first cycle performed after the formation process has been performed.
[0058] In this case, the formation process may include a primary process in which charging and discharging are performed under conditions of CC / CV, cut-off voltage of 0.005V to 1.5V, and 0.1C-rate, and a secondary process in which charging and discharging are performed under conditions of CC / CV, cut-off voltage of 0.005V to 1.0V, and 0.1C-rate. However, it goes without saying that the present invention is not limited by the formation process conditions of the test battery (half cell), and any formation process that is normally performed in a battery conventionally used for testing the electrochemical properties of a negative electrode material may be used.
[0059] In addition, the half cell includes a negative electrode including a negative electrode current collector and a negative electrode active material layer including a negative electrode material according to an embodiment of the present invention, the negative electrode being located on at least one surface of the current collector; a counter electrode being a metallic lithium foil; and a negative electrode and a counter electrode; and an electrolyte in which LiPF6 is dissolved at a concentration of 1M in a mixed solvent in which ethylene carbonate and diethyl carbonate are mixed in a volume ratio of 1:1. The electrochemical characteristics of the half cell may be measured at room temperature.
[0060] In one embodiment, C50 / C1*100 in Equation 1 can be 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more.
[0061] Such cycle characteristics mean that the storage and release of lithium ions in the anode material is substantially completely reversible, that there is substantially no capacity reduction (deterioration of the anode material, deterioration of the electrical contact of the anode material in the anode active material layer, formation of irreversible products, etc.) over 50 repeated charge and discharge cycles, and that the battery has an extremely excellent capacity retention rate.
[0062] In one embodiment, the C50 can be 1150 mAh / g or more, 1200 mAh / g or more, 1250 mAh / g or more, 1300 mAh / g or more, 1350 mAh / g or more, or 1450 mAh / g or more, and can be substantially 2450 mAh / g or less.
[0063] In one embodiment of the present invention, in an X-ray diffraction pattern of a negative electrode material using CuKα radiation, the ratio (A1 / A2) between the area of a first peak (A1) located in a diffraction angle 2θ range of 10° to 27.4° and the area of a second peak (A2) located in a diffraction angle 2θ range of 28±0.5° may be 0.8 to 8, specifically 0.8 to 6, and more specifically 0.8 to 5.5.
[0064] In this case, the area of each peak in the X-ray diffraction pattern means the integrated area occupied by each peak. Here, the integrated area may be the integrated area obtained by fitting the peak from which the noise level has been removed using a Gaussian function and / or a Lorentzian function, but any method for deriving the area of an X-ray diffraction (XRD) peak known in the art may be used without limitation as long as the areas of the first and second peaks are derived in the same manner.
[0065] As a specific example, a peak analyzer tool function of the Origine program, which is one of application software, can be used to remove noise levels around the peaks to be separated, and a Gaussian function can be applied to separate the peaks into two, and then the area of the XRD peaks can be calculated, but the present invention is not limited thereto.
[0066] In one specific example, the ratio (L1 / L2) of the half width at half maximum (FWHM(L1)) of the first peak to the half width at half maximum (FWHM(L2)) of the second peak in the X-ray diffraction pattern can be 1 to 20, specifically 3 to 18, more specifically 6 to 15, and even more specifically 6.5 to 13.
[0067] As another specific example, the intensity ratio (I1 / I2) between the maximum intensity (I1) of the first peak and the maximum intensity (I2) of the second peak may be 0.05 to 1.25, specifically 0.05 to 1.05, and more specifically 0.08 to 0.75. In this case, the first peak may be derived from amorphous silicon oxide, and the second peak may be derived from crystalline silicon. In this way, the negative electrode material of the secondary battery containing the amorphous silicon oxide can act as a buffer against the volume expansion during charging of the secondary battery, and therefore can have an excellent capacity retention rate.
[0068] The negative electrode material for secondary batteries according to another aspect (II) of the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of at least one of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix, wherein the ratio (A1 / A2) between the area of a first peak (A1) located in a range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of a second peak (A2) located in a range of 28±0.5° is 0.8 to 6, and the following formula 2 is satisfied.
[0069] (Formula 2) 1 <WN(Si) / WN(ref)
[0070] In Equation 2, WN(ref) is the central wavenumber of the Raman peak of bulk single crystal silicon, and WN(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material.
[0071] In this case, in formula 2, the ratio between the central wave number of the Raman peak of the bulk single crystal silicon and the central wave number of the Raman peak of the nanoparticle-shaped silicon contained in the negative electrode material is a parameter indicating the type and magnitude of the stress (residual stress) remaining in the silicon nanoparticles dispersed and contained in the matrix. In addition, in formula 2, the term bulk single crystal silicon should be interpreted as meaning silicon of a size that substantially exhibits the physical properties of bulk single crystal silicon, and from the viewpoint of providing a clear comparison standard and ensuring ease of purchase, bulk single crystal silicon can mean a single crystal silicon wafer having a thickness of the sub-mm order, specifically, a thickness of 0.4 to 0.7 mm.
[0072] Specifically, in formula 2, WN(Si) / WN(ref) exceeding 1 means that the central wavenumber of the Raman peak of the nanoparticle silicon contained in the negative electrode material shifts to a longer wavenumber (shorter wavelength in the wavelength of Raman scattered light) compared to bulk single crystal silicon, which means that the nanoparticle silicon has residual compressive stress.
[0073] As described above, the negative electrode material for secondary batteries according to the present invention includes silicon nanoparticles dispersed and contained in a matrix and having residual compressive stress, and the ratio (A1 / A2) between the area of the first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of the second peak (A2) located in the range of 28±0.5° satisfies 0.8 to 6. As a result, the negative electrode material for secondary batteries according to the present invention has improved mechanical properties and electrochemical properties due to the silicon nanoparticles having uniform residual compressive stress, and in particular has the advantage of having a high discharge capacity as well as a capacity retention rate at a level that enables the practical commercialization of secondary batteries equipped with the silicon-based negative electrode material.
[0074] In detail, the compressive stress, which is the main residual stress of the silicon nanoparticles contained in the negative electrode material according to the present invention and dispersed in the matrix, can be uniform due to the crystallographic characteristics in which the ratio (A1 / A2) between the area of the first peak (A1) and the area of the second peak (A2) in the X-ray diffraction pattern satisfies 0.8 to 6.
[0075] In Equation 2, the Raman peak of silicon in each of bulk single crystal silicon and nanoparticle silicon is 500 to 540 cm in the Raman spectrum of silicon. -1 Area, specifically 510~530cm -1 Area, more specifically 515~528cm -1 It can refer to the Raman peak located in the region. The wave number corresponding to the center may refer to the wave number having the maximum intensity value in the peak. In this case, when there are two or more Raman peaks in the above-mentioned Raman shift region, the peak with the highest intensity may correspond to the Raman peak of silicon in formula 2, and when two or more Raman peaks overlap each other to show a bimodal shape, the wave number having the maximum intensity value in the peak with the higher intensity among the bimodal peaks may correspond to the central wave number of the peak.
[0076] As one example, in a 20 mm x 20 mm test piece (negative electrode material), when stress analysis is performed on silicon nanoparticles at 20 different random positions, the compressive stress can be 80% or more, substantially 85% or more, or even substantially 90% or more, and although there is no upper limit, it can be substantially 99% or less.
[0077] The macro-scale anode material contains silicon nanoparticles with residual compressive stress throughout the specimen, enabling the commercialization of secondary batteries equipped with silicon-based anode materials due to significantly improved mechanical and electrochemical properties.
[0078] In addition, the difference between WN(Si) and WN(ref) (WN(Si)-WN(ref)) is a parameter that directly indicates the magnitude of the residual compressive stress possessed by the silicon nanoparticles.
[0079] Specifically, the difference between WN(Si) and WN(ref) is 0.1 cm. -1 More than 0.2cm -1 More than 0.3cm -1 More than 0.4cm -1 More than 0.5cm -1 More than 0.6cm -1 More than 0.7cm -1 More than 0.8cm -1 More than 0.9cm -1 More than 1.0cm -1 Over 1.1cm -1 More than 1.2cm -1 Over 1.3cm -1 Over 1.4cm -1 Over 1.5cm -1 More than 1.6cm -1 Over 1.7cm -1 More than 1.8cm -1 More than 1.9cm -1 Over 2.0cm -1 Over 2.1cm -1 More than 2.2cm -1 Over 2.3cm -1 Over 2.4cm -1 Over 2.5cm -1 More than 2.6cm -1 Over 2.7cm -1 More than 2.8cm -1 More than 2.9cm -1 3.0cm or more -1 Over 3.1cm -1 More than 3.2cm -1 Over 3.3cm -1 Over 3.4cm -1 Over 3.5cm -1 More than 3.6cm -1 Over 3.7cm -1 More than 3.8cm -1 More than 3.9cm -1 More than 4.0cm -1 It can be more than 6.0 cm-1 Less than 5.5cm -1 It can be the following:
[0080] In addition to or independently of the difference between the central wavelengths of the Raman peaks of the bulk single crystal silicon and the nanoparticle silicon contained in the anode material, the full width at half maximum (FWHM) of the Raman peak of the nanoparticle silicon contained in the anode material may be greater than the full width at half maximum (FWHM) of the Raman peak of the bulk single crystal silicon. The greater full width at half maximum (FWHM) value compared to the bulk single crystal silicon may be due to the structure in which the silicon contained in the anode material is dispersed and contained in the matrix in the form of very fine particles. Specifically, the full width at half maximum (FWHM) of the Raman peak of the nanoparticle silicon contained in the anode material is 4 to 20 cm. -1 , 6~20cm -1 , 6~18cm -1 , 6~16cm -1 , 8~20cm -1 , 8~18cm -1 , 8~16cm -1 , 10~20cm -1 , 10~18cm -1 , or 10~16cm -1 It can be, but is not necessarily limited to,
[0081] In addition to this, or independently of this, the nanoparticle silicon contained in the negative electrode material is -1 ) on the Raman spectrum, +20 cm -1 Intensity (K1) at position (wave number) and -20cm -1 The intensity (K2) at the position (wave number) can be significantly different from each other, -20 cm -1 Intensity (K2) at position (wave number) is +20cm -1 The intensity (K1) at the position (wave number) can be larger than that at the position (wave number). In this case, "significantly different" can mean that the ratio of K2 / K1 is 1.20 or more. Such asymmetry of the Raman peak of silicon (long tail in the short wave number direction) is also due to residual pressure. This may be due to the structure in which silicon nanoparticles having compressive stress are dispersed and contained in a matrix.
[0082] In addition, when performing a 2D mapping analysis based on the Raman signal of silicon for the anode material, the difference between the maximum and minimum shifts defined by the following formula 3 was 5 cm -1 It can be the following:
[0083] (Formula 3) deviation=WN i (Si)-WN(ref)
[0084] In Equation 3, WN(ref) is the same as in Equation 2, and WN i (Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the anode material in one pixel, which is a unit analysis area during mapping analysis. In this case, the shift in Equation 3 can be calculated from each pixel only for pixels in which the Raman signal of silicon is detected in the two-dimensional Raman map obtained by two-dimensional mapping analysis, and it goes without saying that the maximum and minimum values refer to the maximum and minimum values of the shifts calculated by Equation 3.
[0085] Based on the two-dimensional Raman map of silicon obtained by two-dimensional mapping analysis of the anode material based on the Raman signal of silicon, the difference between the maximum and minimum shift values (shifts) of the central wavenumber of the silicon peak relative to bulk single crystal silicon according to Equation 3 is an index showing the uniformity of the residual compressive stress of the silicon nanoparticles dispersed and contained in the anode material. The difference between the maximum and minimum shift values based on the two-dimensional Raman map is 5.0 cm. -1 Below, 4.5cm -1 Below, 4.0cm -1 Below, 3.5cm -1 Below, 3.0cm -1 Below, 2.5cm -1 Less than or equal to 1.0 cm -1 The following can be satisfied, and the difference between the maximum and minimum values is practically 0.1 cm. -1 More than 0.5cm -1The difference between the maximum value and the minimum value means that most, or substantially all, of the silicon nanoparticles contained in the negative electrode material have residual compressive stress, and further means that the magnitude of the compressive stress remaining in most, or substantially all, of the silicon nanoparticles contained in the negative electrode material is substantially the same.
[0086] Experimentally, the Raman spectrum of silicon contained in the anode material was measured at room temperature (20-25°C), under atmospheric pressure, with an excitation laser wavelength of 532 nm, a laser power of 0.5 mW, and a spectrometer resolution of 1 cm. -1 The measurement may be performed under the conditions of 1 g of negative electrode material and 15 s of detector exposure time.
[0087] Experimentally, 2D Raman mapping of the anode material using the Raman signal of silicon was performed with the following conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 The measurement may be performed under a mapping condition of a mapping size of 14 μm×14 μm, or may be performed at room temperature and atmospheric pressure.
[0088] As a specific example, in a 20 mm x 20 mm test piece, when a shift analysis is performed based on the Raman signal of silicon at 20 different random positions, the difference between the maximum and minimum shift values defined by the above formula 3 is 5.0 cm. -1 Below, 4.5cm -1 Below, 4.0cm -1 Below, 3.5cm -1 Below, 3.0cm -1 Below, 2.5cm -1 Less than or equal to 1.0 cm -1 The following can be satisfied, and the difference between the maximum and minimum values is practically 0.1 cm. -1 More than 0.5cm -1This is because the residual silicon nanoparticles in the entire test piece, i.e., substantially the entire test piece, are not limited to the mapping area. This means that the magnitude of the compressive stress applied to the specimen is substantially the same.
[0089] In this case, the Raman spectrum and two-dimensional Raman mapping used in the shift analysis may be measured under the same conditions as described above.
[0090] The negative electrode material for secondary batteries according to one embodiment (III) of the present invention is in the form of particles including a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of one or more of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix, the particles having a compressive strength (St) of 100 MPa or more, and an area ratio (A1 / A2) between an area of a first peak (A1) located in a range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and an area of a second peak (A2) located in a range of 28±0.5° satisfies 0.8 to 6.
[0091] As is known, the compressive strength St of a particle is calculated by the formula [ka] where P is the applied force, d is the particle diameter, and L is the particle length, which can be measured using a micro-compression tester (for example, MCT-W500-E, Shimadzu).
[0092] Specifically, the particle compressive strength of the particulate negative electrode material for secondary batteries can be 100 MPa or more, 105 MPa or more, 110 MPa or more, 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, or 160 MPa or more, and can be substantially 250 MPa or less, more substantially 200 MPa or less.
[0093] The negative electrode material for secondary batteries according to the present invention is in the form of particles containing silicon nanoparticles dispersed in the matrix, and exhibits excellent compressive strength of 100 MPa or more. In an X-ray diffraction pattern using CuKα rays, the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° and the area of a second peak (A2) located in the range of 28±0.5° satisfies 0.8 to 6, thereby providing improved mechanical properties and electrochemical properties. In particular, the negative electrode material for secondary batteries according to the present invention has the advantage of having a high discharge capacity as well as a capacity retention rate at a level that enables practical commercialization of secondary batteries equipped with the silicon-based negative electrode material.
[0094] In addition, the negative electrode material having excellent particle compressive strength means that the particulate negative electrode material is not physically damaged during the electrode manufacturing process, which is already established in the field of conventional secondary batteries, from the production of a negative electrode material slurry, to the application of the slurry on a current collector, drying, and rolling (calendering), and that damage to the electrode (negative electrode) pore structure is also prevented, and stable and homogeneous contact with the electrolyte can be guaranteed as designed. As a result, the negative electrode material for secondary batteries of the present invention has the advantage of ensuring structural integrity and achieving stable battery performance.
[0095] In detail, the mechanical properties of the negative electrode material having excellent particle compression strength include the residual compressive stress of nanoparticle silicon, and are physical properties that can be realized by the residual stress present in the negative electrode material. In this case, the residual stress of the silicon nanoparticles dispersed and contained in the matrix contained in the negative electrode material can be in the form of tensile stress, compressive stress, or a mixture of tensile stress and compressive stress. The compressive stress, which is the main residual stress, can be made uniform by the crystallographic characteristics in which the ratio (A1 / A2) between the area of the first peak (A1) and the area of the second peak (A2) in the aforementioned X-ray diffraction pattern satisfies 0.8 to 6.
[0096] Moreover, the aforementioned mechanical strength can be further enhanced by a matched interface between the silicon nanoparticles and the matrix, which creates a stress field in the matrix surrounding the silicon nanoparticles with residual compressive stress.
[0097] Here, the residual compressive stress of the nanoparticle silicon that realizes the mechanical properties of the negative electrode material can be determined by the central wavenumber of the Raman peak of the nanoparticle silicon based on the central wavenumber of the Raman peak of the bulk single crystal silicon, as described above.
[0098] The negative electrode material for secondary batteries according to another aspect (IV) of the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix, and has a hardness of 4.0 GPa or more in a nanoindentation test, a Young's modulus of elasticity of 40 GPa or more, and a ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of a second peak (A2) located in the range of a diffraction angle 2θ of 28±0.5° in an X-ray diffraction pattern using CuKα rays, of 0.8 to 6.
[0099] Hereinafter, with regard to the mechanical properties of the negative electrode material for secondary batteries, all properties are those at room temperature (20 to 25° C.) unless a specific temperature is specified.
[0100] Here, the nanoindentation test was performed in accordance with ASTM E2546, ISO 14577-1 E, ISO 14577-2 E, and ISO 14577-3 E. As is well known, the elastic modulus E is calculated by the formula: [ka] Here, E* is the elastic modulus of the indenter, and ν is the Poisson's ratio of the Berkovich indenter, which is assumed to be 0.3. The nanoindentation test using the Berkovich indenter may be performed under the conditions of a maximum load of 50 mN and a load application rate of 100 mN / min. The strength and elastic modulus measured by the nanoindentation test may be average values of physical properties obtained by performing the nanoindentation test in a matrix form of 5×5 to 25×25, with the distance between the indentations being at least 10 μm or more based on the indentations made by the indenter. In this case, the negative electrode material sample to be subjected to the nanoindentation test may be prepared by mounting and polishing a plate-shaped bulk negative electrode material.
[0101] Specifically, the negative electrode materials for secondary batteries have a strength (indentation strength) of 4.0GPa or more, 4.5GPa or more, 5.0GPa or more, 5.5GPa or more, 6.0GPa or more, 6.5GPa or more, 7.0GPa or more, 7.5GPa or more, 8.0GPa or more, 8.5GPa or more, 9.0GPa or more, 9.5GPa or more, 10.0GPa or more, 10.2GPa or more, 10.4GPa or more, 10 The secondary electric field strength can be 1.6 GPa or more, 10.8 GPa or more, 11.0 GPa or more, 11.2 GPa or more, 11.4 GPa or more, 11.6 GPa or more, 11.8 GPa or more, 12.0 GPa or more, 12.2 GPa or more, 12.4 GPa or more, 12.6 GPa or more, 12.8 GPa or more, or 13.0 GPa or more, and can be substantially 25.0 GPa or less, more substantially 20.0 GPa or less. The elastic modulus of the negative electrode material for a battery can be 40 GPa or more, 41 GPa or more, 42 GPa or more, 43 GPa or more, 44 GPa or more, 45 GPa or more, 50 GPa or more, or 55 GPa or more, as determined by a nanoindentation test, and can be substantially 250 GPa or less, more substantially 200 GPa or less.
[0102] As described above, the negative electrode material for secondary batteries according to the present invention includes silicon nanoparticles dispersed in a matrix, and exhibits high strength of 4.0 GPa or more and excellent elastic modulus (Young's modulus) of 40 GPa or more as measured in a nanoindentation test. In an X-ray diffraction pattern using CuKα rays, the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° and the area of a second peak (A2) located in the range of 28±0.5° satisfies 0.8 to 6, thereby providing improved mechanical properties and electrochemical properties. The negative electrode material has an excellent discharge capacity and a capacity retention rate at a level that enables practical commercialization of secondary batteries including the silicon-based negative electrode material.
[0103] In addition, the negative electrode material having high strength and excellent elasticity, together with the excellent particle compressive strength characteristics described above, not only prevents physical damage to the particulate negative electrode material during the conventional electrode manufacturing process, particularly the rolling process, but also stably maintains the pore structure of the electrode (negative electrode), thereby further improving the structural integrity of the negative electrode material for secondary batteries of the present invention.
[0104] The negative electrode material for secondary batteries according to another aspect (V) of the present invention includes, based on elemental components, a matrix containing silicon (Si), a doping element (D) selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, and oxygen (O); and silicon nanoparticles dispersed and contained in the matrix; the negative electrode material has a compositional uniformity that satisfies the following formula 4, and a ratio (A1 / A2) between an area (A1) of a first peak located in a diffraction angle 2θ range of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and an area (A2) of a second peak located in a diffraction angle 2θ range of 28±0.5° satisfies 0.8 to 6.
[0105] (Formula 4) B / A≦0.65
[0106] In this case, A and B in Equation 4 are the average (A) and standard deviation (B) of the content (wt%) of the doping element measured at 100 arbitrary points on a cross section crossing the center of the negative electrode material.
[0107] Specifically, A and B may be the average content (wt%, A) and standard deviation (B) of the doping element calculated from any 100 points in a line profile of the doping element across the center of the cross section of the negative electrode material, and more specifically, B / A in Equation 3 may be 0.65 or less, 0.60 or less, 0.55 or less, 0.50 or less, 0.40 or less, or 0.30 or less, and may be 0.2 or more.
[0108] In Equation 4, B / A is a parameter that indicates the composition uniformity of the anode material based on the doping element (D). The excellent composition uniformity of B / A that satisfies the above-mentioned range allows the anode material to exhibit uniform mechanical and electrochemical properties.
[0109] In the negative electrode material for secondary batteries that satisfies the above-mentioned composition uniformity, the matrix based on the elemental components may contain at least one doping element (D) selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, silicon (Si), and oxygen (O), and the matrix based on the compound components may contain silicon oxide and a composite oxide of the doping element and silicon. Therefore, the composition uniformity of the doping element defined in Equation 4 may correspond to the composition uniformity of the composite oxide, but is not necessarily limited thereto. It is not.
[0110] Here, the content and linear composition of the doping element are analyzed experimentally using an Electron Probe Micro Analyzer (EPMA) or an Energy Dispersive X-ray Spectroscopy (EDX) equipped with a transmission electron microscope or a scanning electron microscope. The method may be performed using, but is not limited to, dispersive X-ray spectroscopy (EDS).
[0111] In addition, in one embodiment, a negative electrode material including a plurality of negative electrode material particles may have a composition uniformity between particles according to the following formula 5.
[0112] (Formula 5) 1.3≦UF(D)
[0113] In formula 5, UF(D) is the value obtained by dividing the average doping element composition among the negative electrode material particles by the standard deviation of the doping element composition based on the weight percent composition. In this case, the number of negative electrode material particles can be 10 to 500, substantially 50 to 300, and more substantially 100 to 200.
[0114] Specifically, UF(D) in formula 5 can be 1.3 or more, 1.5 or more, 2 or more, 2.5 or more, 3 or more, or 5 or more, and can be substantially 8 or less. The above-mentioned UF(D) is a parameter indicating the composition uniformity between anode material particles in anode material containing a plurality of anode material particles, and when UF(D) in formula 5 satisfies the above-mentioned range, the anode material containing a plurality of anode material particles has excellent composition uniformity, and there is an advantage that the mechanical properties and electrochemical properties of the anode material are more uniform even if a plurality of anode material particles are included.
[0115] A negative electrode material for a secondary battery according to another aspect (VI) of the present invention includes: a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post transition metals, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix; and based on a negative electrode active material layer formulated with 80% by weight of the negative electrode material, 10% by weight of a conductive material, and 10% by weight of a binder, a volume change of the negative electrode active material layer is within 60% upon charging to 0.005 V, and a ratio (A1 / A2) between an area (A1) of a first peak located in a diffraction angle 2θ range of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and an area (A2) of a second peak located in a diffraction angle 2θ range of 28±0.5° satisfies 0.8 to 6.
[0116] Conventional silicon-based anode materials, which have a theoretical capacity of up to 4,200 mAh / g, have the disadvantage that they undergo a volume change of more than 300% during charging, causing the anode material to detach from the current collector, resulting in a significant decrease in capacity retention.
[0117] In contrast, the negative electrode material for secondary batteries according to the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and contained in the matrix, and based on a negative electrode active material layer formulated with 80 wt % of the negative electrode material, 10 wt % of the conductive material, and 10 wt % of the binder, when loaded to 0.005 V, the volume change of the negative electrode active material layer is within 60%, and the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° and the area of a second peak (A2) located in the range of 28±0.5° in an X-ray diffraction pattern using CuKα rays satisfies 0.8 to 6, thereby not only having improved mechanical properties and electrochemical properties, but also being able to realize a secondary battery having the silicon-based negative electrode material together with excellent discharge capacity. The advantage is that it has a capacity retention rate at a commercially viable level.
[0118] Specifically, the above-mentioned volume change (%) is a volume change of the negative electrode active material layer containing the negative electrode material, and may be defined as [thickness of the negative electrode active material layer after lithiation-thickness of the negative electrode active material layer before lithiation] / thickness of the negative electrode active material layer before lithiation*100, and experimentally, the thicknesses of the negative electrode active material layer before and after lithiation may be measured by observation photographs using a scanning electron microscope, etc.
[0119] When a battery including a negative electrode active material layer is charged to 0.005 V, the volume change is within 60%, specifically within 50%, 40%, 30%, 20%, or 15%, which means that a significantly smaller volume change occurs compared to conventional silicon-based negative electrode materials, and this means that major problems with conventional silicon-based negative electrode materials, such as electrode cracking and / or detachment due to volume expansion, are largely eliminated.
[0120] The negative electrode active material layer, which is the standard for testing the degree of volume expansion of the negative electrode material, may contain 80% by weight of the above-mentioned negative electrode material, a conductive material, specifically, 10% by weight of carbon black, and 10% by weight of a binder, specifically, 5% by weight of carboxymethyl cellulose and 5% by weight of styrene butadiene rubber. The current collector in the negative electrode provided with the negative electrode active material layer may be copper foil. Although not particularly limited, the thickness of the negative electrode active material layer before lithiation may be at a level of 15 to 25 μm.
[0121] In this case, the charging may be performed by a charge / discharge test according to the following charge / discharge cycle conditions using a half cell in which a negative electrode containing a negative electrode material and a counter electrode are metallic lithium foil, and may be performed by charging to 0.005 V in a charge / discharge cycle, specifically, in the first charge / discharge cycle.
[0122] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0123] The negative electrode material for secondary batteries according to another aspect (VII) of the present invention comprises a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of at least one of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix; and in a dQ / dV graph obtained by a charge-discharge test under the following charge-discharge cycle condition 1 using a half cell in which a counter electrode is a metallic lithium foil, Li 3.75A lithium insertion peak corresponding to a Si reaction is present, the discharge capacity in the first charge / discharge cycle under the charge / discharge cycle condition 2 described below is 1200 mAh / g or more, and the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of a second peak (A2) located in the range of a diffraction angle 2θ of 28±0.5° satisfies 0.8 to 6.
[0124] Charge / discharge cycle condition 1: CC / CV, cut-off voltage 0.005V~1.0V, 0.1C-rate
[0125] Charge / discharge cycle condition 2: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0126] Specifically, the negative electrode material for secondary batteries according to the present invention includes a matrix containing silicon oxide, a composite oxide of silicon and a doping element selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and contained in the matrix, and has a dQ / In the dV graph, Li 3.75 A lithium insertion peak corresponding to a Si reaction is present, the discharge capacity in the first charge / discharge cycle is 1200 mAh / g, and the ratio (A1 / A2) between the area of a first peak (A1) located in the range of a diffraction angle 2θ of 10° to 27.4° in an X-ray diffraction pattern using CuKα rays and the area of a second peak (A2) located in the range of 28±0.5° satisfies 0.8 to 6. This not only provides an excellent discharge capacity of 1200 mAh / g or more, but also improved mechanical properties and electrochemical properties, and a capacity retention rate at a level that enables practical commercialization of secondary batteries equipped with silicon-based negative electrode materials.
[0127] More specifically, the dQ / dV graph may be a graph showing the relationship between the differential value dQ / dV obtained by differentiating the battery capacity (discharge capacity) Q in the first charge / discharge cycle with respect to the negative electrode potential V, based on the metallic lithium foil of the half-cell, and the potential V.
[0128] At this time, Li on the dQ / dV graph 3.75 The lithium insertion peak corresponding to the Si reaction may refer to a peak located in a voltage range of 0.005V to 0.100V, specifically, in a voltage range of 0.005V to 0.050V, and more specifically, in a voltage range of 0.005V to 0.040V.
[0129] That is, the negative electrode material for secondary batteries according to the present invention is such that lithium insertion is Li 3.5 Li beyond Si 3.75 This means that up to Si is performed, and Li 3.75 By inserting lithium into Si, the capacity of the negative electrode material can be improved.
[0130] As a substantial example, after the chemical formation step, when the half-cell is charged and discharged according to cycle conditions, i.e., the first discharge capacity after the chemical formation step, can be 1200 mAh / g or more, 1250 mAh / g or more, 1300 mAh / g or more, 1350 mAh / g or more, 1400 mAh / g or more, or 1500 mAh / g or more, and can be substantially 2500 mAh / g or less.
[0131] The negative electrode material for a secondary battery according to another embodiment (VIII) of the present invention includes a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix and having a residual compressive stress.
[0132] The residual compressive stress of the nanoparticles of silicon dispersed in the matrix, and further the stress field formed in the matrix around the silicon nanoparticles due to the residual compressive stress of the silicon and the coherent interface formed between the silicon nanoparticles and the matrix, are one aspect of the anode material based on the Raman spectrum described above, another aspect of the anode material based on the mechanical properties, and another aspect of the anode material based on the electrochemical properties during lithiation, and can appear as physical properties or measurable parameters of the anode material.
[0133] The negative electrode material in the present invention can satisfy one or more of the above-mentioned aspects (I to VIII), two or more of the aspects, three or more of the aspects, four or more of the aspects, five or more of the aspects, six or more of the aspects, seven or more of the aspects, or all of the aspects I to VIII.
[0134] Hereinafter, unless specifically stated as being limited to "one aspect of the present invention", the contents described below apply to each of all aspects provided by the present invention.
[0135] In one embodiment, the anode material contains doping elements selected from the group consisting of silicon, oxygen, alkali and alkaline earth metals, and post-transition metals, based on elemental composition. The silicon may include a silicon component in an elemental silicon state and a silicon component in an oxide state, and the silicon component in the oxide state may include an oxide state of silicon alone, a composite oxide state of silicon and a doping element, or both. The doping element may include a doping element component in an oxide state, and the doping element in an oxide state may include an oxide state of the doping element alone, a composite oxide state of silicon and a doping element, or both.
[0136] Based on the compound components, the anode material may contain silicon oxide, a composite oxide of a doping element and silicon, or a mixture thereof, as well as elemental silicon (Si). Silicon oxide is SiO x , x can be a real number from 0.1 to 2, and the complex oxide is Dl S m O n where D is a doping element, l is a real number from 1 to 6, m is a real number from 0.5 to 2, and n is a real number that satisfies charge neutrality by the oxidation numbers of D and Si, and l and m. As an example, when D is Mg, the composite oxide can include one or more oxides selected from MgSiO3 and Mg2SiO4, but in the present invention, D and the composite oxide are not necessarily limited to an oxide between Mg and Mg-Si.
[0137] Based on the microstructure, the negative electrode material may contain a matrix containing silicon oxide, a composite oxide of silicon and a doping element selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof, and a dispersed phase containing silicon nanoparticles. The dispersed phase may be uniformly dispersed and contained within the matrix.
[0138] In one embodiment, the silicon nanoparticles may be crystalline, amorphous, or a combination of crystalline and amorphous phases, or may be substantially crystalline.
[0139] In one embodiment, the matrix may be crystalline, amorphous, or a composite phase of crystalline and amorphous. In particular, the matrix may be crystalline or a composite phase of crystalline and amorphous. Specifically, the matrix may include a composite oxide of amorphous, crystalline, or a composite of amorphous and crystalline silicon oxide.
[0140] The interface between the silicon nanoparticles and the matrix may include a coherent interface, an incoherent interface, a semi-coherent interface, a substantially coherent interface, or a semi-coherent interface, and may further include a substantially coherent interface. As is known, a coherent interface is an interface where the lattices of the two interfacing materials maintain lattice continuity at the interface, and a semi-coherent interface is an interface where a lattice mismatch exists partially, but such a lattice mismatch can be regarded as a defect such as a dislocation. Thus, in a negative electrode material having a coherent or semi-coherent interface between the silicon nanoparticles and the matrix, the matrix region in contact with the silicon nanoparticles may be crystalline, and more specifically, may be a crystalline silicon oxide, a crystalline composite oxide, or a mixture thereof. Experimentally, the interface structure of a coherent interface, an incoherent interface, or a semi-coherent interface can be determined by observation with a high-magnification scanning electron microscope, which is a well-known fact to those skilled in the art.
[0141] In one embodiment, the average diameter of the silicon nanoparticles is 10 0 Nanometer order ~ 10 1 The size may be on the order of nanometers, specifically 1 to 50 nm, 2 to 40 nm, 2 to 35 nm, 2 to 30 nm, 2 to 20 nm, or 2 to 15 nm, but is not limited thereto. However, silicon nanoparticles at a level of 30 nm or less may be advantageous because they form a coherent interface with the matrix as a whole, and stress is formed in a wider area of the matrix due to the compressive stress remaining in the silicon nanoparticles. Experimentally, silicon nanoparticles The average diameter may be calculated by measuring the size of silicon nanoparticles in the negative electrode material using an image observed with a transmission electron microscope, and averaging the sizes measured for 10 or more, 20 or more, or 30 or more silicon nanoparticles.
[0142] In one embodiment, the doping element may be one or more selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi). Thus, the composite oxide may be an oxide between silicon and one or more elements selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi). The mechanical and electrochemical properties of the negative electrode material can be further improved by the synergistic effect between the composite oxide and the silicon nanoparticles having residual compressive stress. In order to favor the formation of a matching interface with the silicon nanoparticles, the doping element may be one or more elements selected from the group of alkali metals and alkaline earth metals, specifically lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba), and more preferably, may be one or more elements selected from the group of alkaline earth metals, specifically magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba). Most preferably, in terms of the easy formation of a matching interface and the synergistic effect with the silicon nanoparticles having residual compressive stress, the doping element may include magnesium. As described above, the doping element may be contained in the negative electrode material in the form of a complex oxide with silicon and / or an oxide of the doping element, or may be contained in the negative electrode material mainly in the form of a complex oxide. Specifically, when the matrix contains the doping element in the form of a complex oxide with silicon, the complex oxide may include a crystalline material, and more substantially the complex oxide may be crystalline. Thus, the matrix may contain a crystalline complex oxide.
[0143] In one embodiment, the silicon oxide contained in the matrix may be SiOx, where x is a real number between 0.1 and 2, more specifically, a real number between 0.5 and 2, and may include a first silicon oxide and a second silicon oxide having different x. As a substantial example, the silicon oxide contained in the matrix may be SiO x1 (x1 is a real number between 1.8 and 2) x2 (x2 is a real number of 0.8 to 1.2) and a second silicon oxide. The silicon oxide contained in the matrix may be crystalline, amorphous, or a composite phase of crystalline and amorphous, or may be substantially amorphous.
[0144] In one embodiment, the anode material may contain 15-50% by weight of nanoparticulate silicon and the remainder matrix.
[0145] In one specific example, the matrix of the negative electrode material can contain both silicon oxide and composite oxide, and when the weight part of the composite oxide is A based on 100 parts by weight of silicon oxide, and the concentration of the doping element in the negative electrode material based on weight % is B, the ratio A / B can be 2 to 50, 2 to 40, 2 to 30, or 2 to 20.
[0146] In one embodiment, the anode material may be in particulate form. The particulate anode material may have a particle size typically required for secondary battery applications, for example, 10 0 μm order ~ 10 1 The average diameter may be on the order of μm, specifically, 5 μm to 30 μm, but is not limited thereto.
[0147] In one embodiment, the negative electrode material may further include a coating layer containing carbon, specifically, a surface coating layer coated on the surface of the negative electrode material. Such a surface coating layer can advantageously improve the electrical properties of the negative electrode material. The thickness of the coating layer may be on the order of 2 to 30 nm, but is not necessarily limited thereto.
[0148] In one embodiment, the negative electrode material contains silicon nanoparticles having residual compressive stress, and when electrochemically alloyed with lithium (lithiation), the alloying ratio is 3.5 (or more) to 3.75 moles of lithium per mole of silicon, specifically 3.6 to 3.75 moles. Such a high alloying ratio is very advantageous for high capacity. In addition, in one embodiment, the negative electrode material can have high initial charge / discharge efficiency and capacity retention.
[0149] The present invention includes an anode containing the above-mentioned anode material. The anode can be a secondary battery, specifically a lithium secondary battery anode. The anode can include a current collector; an anode active material layer located on at least one surface of the current collector and containing the above-mentioned anode material, and the anode active material layer can further include a binder and a conductive material that are commonly used in anode materials and anodes of secondary batteries, as necessary.
[0150] The present invention includes a secondary battery including the above-mentioned negative electrode. Specifically, the present invention includes a lithium secondary battery including the above-mentioned negative electrode. The lithium secondary battery may include a positive electrode including a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector; the above-mentioned positive electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte that conducts lithium ions. The positive electrode current collector, the negative electrode current collector, the positive electrode active material and composition of the positive electrode active material layer, the separator, the electrolyte solvent, the electrolyte salt or the concentration of the electrolyte salt, and the like may be materials and compositions that are usually used in lithium secondary batteries. EXAMPLES
[0151] Example 1 The Si, SiO2, and MgO raw materials were charged into a powder mixer in a molar ratio of 6 (Si):4.5 (SiO2):1.5 (MgO), respectively, and mixed homogeneously to produce a mixed raw material. The mixed raw material was then pelletized using a mold.
[0152] The pelletized mixed raw material was placed in a crucible (26 kg) in a vacuum chamber of 0.1 torr or less, heated to 1400° C. to vaporize it, and then condensed on a collection plate at 400° C. to obtain magnesium-doped silicon oxide.
[0153] The obtained magnesium-doped silicon oxide was heat-treated at 850° C. for 20 hours in an Ar atmosphere to produce a bulk-type secondary battery negative electrode material.
[0154] The bulk-type secondary battery anode material was mechanically crushed to an average particle size of 5μm to produce particulate anode material, and the particulate anode material was coated with 5wt% carbon through a CVD process at 850℃ using hydrocarbon gas to produce carbon-coated anode material powder.
[0155] Example 2 The same procedure as in Example 1 was carried out, except that the raw materials were mixed in a molar ratio of 6.5 (Si):4.5 (SiO2):0.5 (MgO).
[0156] Example 3 The same procedure as in Example 1 was carried out, but the raw materials were mixed in a ratio of 6.5 (Si):4.5 (SiO2). The procedure was the same except that the molar ratios were mixed.
[0157] Comparative Example 1 The Si, SiO2, and MgO raw materials were charged into a powder mixer in a molar ratio of 6 (Si): 4.5 (SiO2): 1.5 (MgO), and then mixed homogeneously to produce the raw material.
[0158] 26 kg of the raw materials were placed in a crucible in a vacuum chamber of less than 0.1 torr, then heated to 1400°C to vaporize, and then condensed on a collection plate at 400°C to obtain magnesium-doped silicon oxide. The obtained magnesium-doped silicon oxide (anode material for bulk-type secondary batteries) was mechanically crushed to an average particle size of 5μm to produce particulate anode material, and the particulate anode material was coated with 5% by weight of carbon through a CVD process at 850°C using hydrocarbon gas to produce carbon-coated anode material powder.
[0159] Comparative Example 2 24 kg of a mixed raw material of Si and SiO2 was placed in crucible A, and 2 kg of metallic Mg lump was placed in crucible B. Crucible A was heated to 1,500°C, and crucible B was heated to 900°C to vaporize the raw material, which was then condensed on a collection plate at 900°C to obtain magnesium-doped silicon oxide.
[0160] The obtained magnesium-doped silicon oxide (anode material for bulk-type secondary batteries) was mechanically pulverized to an average particle size of 5 μm to produce a particulate anode material, and the particulate anode material was coated with 5 wt % carbon through a CVD process at 850 °C using hydrocarbon gas to produce a carbon-coated anode material powder.
[0161] Comparative Example 3 The same procedure as in Example 1 was carried out, except that only Si raw material was used and heating was carried out at 2200°C.
[0162] (Experimental Example 1) Deviation of doping element content Using a cross section crossing the center of the magnesium-doped silicon oxide before pulverization (Comparative Example 2) and the bulk-type secondary battery negative electrode material obtained by heat treatment (Example 1) as a reference, the average content (wt%) of the doping element calculated by measuring 100 arbitrary points in the linear composition crossing the center of the cross section through EDS (Electron Disperse Spectroscopy) was calculated as A and the standard deviation of the content was calculated as B, which are shown in Figure 1. As a result of the composition analysis, the B / A of the negative electrode material sample prepared in Example 1 was 0.25, and in the case of Comparative Example 2, the B / A was 0.69.
[0163] Furthermore, after crushing the negative electrode material of Example 1, 150 negative electrode material particles were sampled and the composition uniformity of the doping element contained between the negative electrode material particles was analyzed. At this time, UF(D), which is the value obtained by dividing the average doping element composition (wt%) between the negative electrode material particles by the standard deviation of the doping element composition, was confirmed to be 6.2.
[0164] (Experimental Example 2) X-ray diffraction (XRD) analysis The crushed negative electrode material was analyzed by X-ray diffraction (XRD, Rigaku D / MAX-2500 / PC, 40 kV, 15 mA, 4°min -1 The structure was confirmed by analysis using Cu-Kα radiation (λ=0.15406 nm).
[0165] FIG. 2 is a diagram showing the XRD patterns of Examples 1 to 3 and Comparative Example 3. As can be seen from the diagram, a peak of crystalline silicon 111 was observed at a position of about 28° in each of Examples 1 to 3 and Comparative Example 3. The peaks in Examples 1 to 3 positioned in the range of diffraction angles 2θ of 10° to 27.4° showed broad peaks, whereas in Comparative Example 3, the peaks in the range of diffraction angles 2θ of 10° to 27.4° showed broad peaks. It was confirmed that there was no peak located in the range of 10° to 27.4°. This shows that Examples 1 to 3 contain amorphous silicon oxide, while Comparative Example 3 does not contain amorphous silicon oxide. As a result, Examples 1 to 3 containing amorphous silicon oxide can act as a buffer against volume expansion during charging of the secondary battery, and therefore may be advantageous in terms of the capacity retention rate of the secondary battery.
[0166] Furthermore, when comparing the ratio (A1 / A2) between the area of the first peak (A1) located in the range of diffraction angle 2θ of 10° to 27.4° in the X-ray diffraction pattern and the area of the second peak (A2) located in the range of 28±0.5°, it was confirmed that Examples 1 to 3 had a ratio in the range of 0.8 to 6.
[0167] Additionally, when comparing the intensity ratios (I1 / I2) between the maximum intensity (I1) of the first peak located in the range of a diffraction angle 2θ of 10° to 27.4° in the X-ray diffraction pattern and the maximum intensity (I2) of the second peak located in the range of 28±0.5°, it was confirmed that Examples 1 to 3 had an intensity ratio in the range of 0.1 to 1.25. As a result of comparative analysis of the ratios (L1 / L2) of the FWHM (L1) of the first peak to the FWHM (L2) of the second peak, it was confirmed that Examples 1 to 3 had an intensity ratio in the range of 6 to 12.
[0168] (Experimental Example 3) Raman analysis After pulverization, the anode material was analyzed using μ-Raman (equipment name: XperRam C, Nanobase, Korea) under the following conditions, with the Raman signal of silicon as the standard. The Raman signal of the anode material powder is shown in FIG. 3. As shown in FIG. 3, the Raman signal (peak center) of silicon in the anode material manufactured in Example 1 is 523.6 cm. -1 It is found that the anode material produced in the comparative example has residual compressive stress, and the anode material produced in the comparative example has residual tensile stress. In addition, the half-width (FWHM) of the Raman signal of the silicon produced in the example 1 was measured, and the half-width (FWHM) was 12 cm. -1 It was confirmed that this is larger than the full width at half maximum (FWHM) of the Raman signal of single crystal silicon (C-Si (Ref.) in Figure 3).
[0169] Analysis conditions: Excitation laser wavelength 532 nm, laser power 0.5 mW, spectrometer resolution 1 cm -1 , 1g of powdered negative electrode material, detector exposure time 15s
[0170] The residual stress in silicon was calculated using the Raman measurement results and the following formula, and the silicon residual stress in the particulate negative electrode material and the silicon residual stress in the bulk negative electrode material were summarized in Table 1. As summarized in Table 1 together with the results of the comparative examples, in the case of the negative electrode material manufactured in Example 1, it can be seen that the silicon has a residual compressive stress of 0.74 GPa in the bulk form and a residual compressive stress of 0.29 GPa in the particulate form, and that in the case of Comparative Example 1, the Si in the amorphous phase and in the case of Comparative Example 2, the Si have tensile stress rather than compressive stress.
[0171] [ka]
[0172] where σ is the residual stress, △ω is the Raman signal of single crystal silicon (Si(ref) in Fig. 3, 520.4 cm -1 ) (=wavenumber of measured Raman signal of silicon−wavenumber of Raman signal of single crystal silicon), where a positive value of Δω indicates compressive stress and a negative value of Δω indicates tensile stress.
[0173] 2D mapping analysis based on the Raman signal of silicon by μ-Raman analysis (equipment name: XperRam C, Nanobase, Korea) of magnesium-doped silicon oxide before crushing (Comparative Example 1) and bulk-type secondary battery anode material obtained by heat treatment (Example 1) The mapping was performed under the following conditions, and the mapping results are shown in Figure 4. In the case of the negative electrode material manufactured in Example 1, Raman peaks of silicon were detected in all pixels, and the shift for each pixel = WNi(Si)-WN(ref) was measured, and it was confirmed that the shift range was 2.86 (minimum value) to 4.58 (maximum value).
[0174] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 , mapping size = 14 μm × 14 μm
[0175] Furthermore, a shift analysis was performed based on the Raman signal of silicon under the above conditions at 20 different random positions selected from the pre-ground negative electrode material of 20 mm x 20 mm size, and it was confirmed that the range of shifts measured at the different positions was 2.42 (minimum value) to 4.86 (maximum value). In addition, a stress analysis of silicon nanoparticles at 20 different random positions confirmed that the silicon nanoparticles had a compressive stress in the range of 88 to 99%.
[0176] (Experimental Example 4) Mechanical Properties The particle strength was measured using a micro compression tester MCT-W manufactured by Shimadzu Corporation. The particle strength was measured for 10 random particles with a diameter of 10 μm, and the measurement results are summarized in Table 1.
[0177] The microcompression tester continuously applies force to particles, and the pressure at which the particles break is defined as the particle strength, which is automatically measured.
[0178] Furthermore, tests were performed using a nanoindentation testing device (Anton Paar, Austria) on cross sections of the magnesium-doped silicon oxide before crushing (Comparative Example 1) and the bulk-type secondary battery negative electrode material obtained by heat treatment (Example 1).
[0179] In the case of nano-indentation test (indenter), the measurement was performed according to the measurement standard of ISO 14577-1 E, using a Berkovich indenter, assuming a Poisson's ratio of 0.3, with a maximum load of 50 mN and a load application rate of 100 mN / min. Based on the indentation marks made by the indenter, the distance between the indentations was at least 10 μm and the indentation was performed in a matrix shape of 5×5 to 25×25, and the calculated strength and elastic modulus are shown in FIG.
[0180] As shown in FIG. 5, the average strength value and the average elastic modulus value of Example 1 obtained by the nano-indentation test were confirmed to be 4.41 GPa and 43.1 GPa, respectively, while the average strength value and the average elastic modulus value of Comparative Example 1 obtained by the nano-indentation test were confirmed to be 2.76 GPa and 30.6 GPa, respectively. As a result of the nano-indentation test, the strength of Example 1 was about 1.6 times and the elastic modulus was about 1.4 times that of Comparative Example 1, indicating that the mechanical properties of Example 1 were significantly improved.
[0181] (Experimental Example 5) Battery Production and Evaluation of Battery Performance The final negative electrode powder was used as the active material, and the active material:conductive material (carbon black):CMC (Carboxymethyl cellulose):SBR (Styrene Butadiene Rubber) was mixed in a weight ratio of 8:1:0.5:0.5, applied to a 17μm thick copper foil, and then dried at 90℃ for 40 minutes. After drying, a 14mm diameter was punched out, and a 16mm diameter lithium metal was used as the counter electrode. A 18mm diameter separator was sandwiched between the electrodes, and the electrolyte was filled to create a CR2032 coin-type half cell. The electrolyte was EC (Ethyl 1M LiPF6 was dissolved in a solvent in which 1:1 volume ratio of ethylene carbonate (PEC) / DEC (Diethyl carbonate) was mixed, and 3wt% of FEC (fluoroethylene carbonate) was used as an additive. The formation process was performed by charging the manufactured battery to 0.005V at a constant current of 0.1C (lithiation), charging at a constant voltage of 0.005V until it reached 0.01C, discharging at a constant current of 0.1C to 1.5V (de-lithiation) (first formation step), charging again at a constant current of 0.1C to 0.005V, charging at a constant voltage of 0.005V until it reached 0.01C, and discharging at a constant current of 0.1C to 1.0V (de-lithiation) (second formation step).
[0182] Charge / discharge cycle conditions: Charge (lithiation) at a constant current of 0.5C to 0.005V, charge at a constant voltage of 0.005V until it reaches 0.05C, then discharge (de-lithiation) at a constant current of 0.5C to 1.0V.
[0183] Number of charge / discharge cycles: 50 After the chemical formation process, the discharge capacity (C1) of the first cycle is summarized as capacity and shown in Table 1. The initial efficiency based on charge and discharge in the first chemical formation step and the capacity retention rate based on C50 / C1*100 after the chemical formation step are also summarized in Table 1. The charge and discharge capacity and capacity retention rate for the first chemical formation step, the second chemical formation step, and the charge and discharge cycle are shown in Figure 6(a) and Figure 6(b), respectively.
[0184] [Table 1]
[0185] Furthermore, the capacities of Examples 2 and 3 were confirmed to be 1418 and 1465 mAh / g, respectively, and the capacity retention rates of Examples 2 and 3 were both confirmed to be 95% or higher, specifically, 99.0% and 100.3%, respectively.
[0186] 7(a) and 7(b) are graphs showing dQ / dV graphs in the first charge-discharge cycle under the charge-discharge cycle conditions of CC / CV, cut-off voltage of 0.005 V to 1.0 V, and 0.1 C-rate for Examples 1 to 3 and Comparative Examples 1 to 3, respectively. Referring to FIG. 7(a), in the cases of Examples 1 to 3, Li 3.5 In addition to the lithium insertion peak corresponding to the Si reaction, 3.75 It can be seen that there is a lithium insertion peak corresponding to the Si reaction. It can be seen that lithiation is carried out at an alloying ratio of 3.75 moles of lithium per mole of silicon.
[0187] On the other hand, as shown in FIG. 7(b), in Comparative Example 1 and Comparative Example 2, Li 3.5 Only the lithium insertion peak for the Si reaction was observed, and the Li 3.75 No lithium insertion peak corresponding to the Si reaction was observed.
[0188] Thus, the negative electrode material according to one embodiment of the present invention converts silicon into lithium 3.5 Li over Si reaction 3.75 Lithium insertion can be performed up to the Si reaction, and it can have excellent capacity.
[0189] Figure 8 is a high-resolution transmission electron microscope (HR-TEM) image of Example 1. From Figure 8, it was confirmed that the average diameter of the crystalline silicon nanoparticles was about 7.1 nm, and the results of a selected area diffraction pattern (SADP) analysis confirmed that the matrix contained crystalline magnesium silicate and that the silicon nanoparticles formed a coherent interface with the crystalline magnesium silicate.
[0190] Although not shown in the figure, the particle size distribution of the ground and carbon-coated negative electrode material powder was measured, and it was found that the particles of the negative electrode material powder had an average particle size (D50) of 7.9 μm.
[0191] 9 is a scanning electron microscope photograph of the cross section and thickness of the negative electrode active material layer containing the negative electrode material of Example 1 before lithiation and a scanning electron microscope photograph of the cross section and thickness of the negative electrode active material layer after lithiation at 0.005V in the third charge / discharge cycle (the first charge / discharge cycle in the life evaluation stage). It was confirmed that the volume expansion rate was only about 15.5% due to the thickness change before and after lithiation. Although not shown in the figure, the volume expansion rate due to the thickness change before and after lithiation of the negative electrode active material layer containing each negative electrode material was confirmed to be 13.4% in Example 2 and 12.5% in Example 3, while it was confirmed to be 27.1%, 30.3% and 271.2%, respectively, in Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0192] As described above, the present invention has been described using specific and limited embodiments and drawings, but these are provided to assist in a more complete understanding of the present invention. The present invention is not limited to the above embodiments, and various modifications and variations are possible from such descriptions by those having ordinary knowledge in the field to which the present invention pertains.
[0193] Therefore, the concept of the present invention should not be limited to the described embodiments, and it can be said that not only the scope of the claims described below, but also all modifications that are equivalent or similar to the scope of the claims fall within the scope of the concept of the present invention.
Claims
1. The present invention comprises a matrix containing a composite oxide of silicon and a doping element selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and contained in the matrix; When a charge-discharge test was performed under the following charge-discharge cycle conditions using a half cell having a metallic lithium foil as a counter electrode, the following formula 1 was satisfied, and the area of the first peak (A 1 ) and the area of the second peak located in the range of 28±0.5° (A 2 ) between the ratio (A 1 / A 2 ) is 0.8 to 6. Charge / discharge cycle conditions: constant current / constant voltage (CC / CV), cut-off voltage 0.005V to 1.0V, 0.5 charge / discharge rate (C-rate) (Formula 1) 95%≦C50 / C1*100 (In formula 1, C1 is the discharge capacity (mAh / g) in the first charge / discharge cycle, and C50 is the discharge capacity in the 50th charge / discharge cycle.)
2. The full width at half maximum (FWHM(L 1 ) and the half width at half maximum (FWHM(L 2 )) to the ratio (L 1 / L 2 2. The negative electrode material for secondary batteries according to claim 1, wherein the molecular weight of the negative electrode material for secondary batteries is 6 to 15.
3. The maximum intensity of the first peak (I 1 ) and the maximum intensity of the second peak (I 2 ) between the intensity ratio (I 1 / I 2 2. The negative electrode material for secondary batteries according to claim 1, wherein the ratio of the stoichiometric ratio of the negative electrode material for secondary batteries to the stoichiometric ratio of the negative electrode material for secondary batteries is 0.05 to 1.
25.
4. 2. The negative electrode material for secondary batteries according to claim 1, wherein the first peak is derived from an amorphous silicon oxide, and the second peak is derived from crystalline silicon.
5. The negative electrode material for secondary batteries according to claim 1, wherein the C50 is 1150 mAh / g or more.
6. 2. The negative electrode material for secondary batteries according to claim 1, wherein the full width at half maximum (FWHM) of the Raman peak of the nanoparticle silicon contained in the negative electrode material is greater than the full width at half maximum (FWHM) of the Raman peak of bulk single crystal silicon.
7. The full width at half maximum (FWHM) of the Raman peak of the nanoparticle silicon contained in the negative electrode material is 4 to 20 cm -1 The negative electrode material for secondary batteries according to claim 6 .
8. The negative electrode material for secondary batteries according to claim 6, which satisfies the following formula 2 based on the Raman signal of silicon. (Formula 2) 1<WN(Si) / WN(ref) (In Equation 2, WN(ref) is the central wave number of the Raman peak of bulk single crystal silicon, and WN(Si) is the central wave number of the Raman peak of nanoparticle silicon contained in the negative electrode material.)
9. In the two-dimensional mapping analysis based on the Raman signal of silicon, the difference between the maximum and minimum shifts defined by the following formula 3 is 5 cm under the following mapping conditions. -1 The negative electrode material for secondary batteries according to claim 8, wherein: Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, Pixel resolution = 1 cm -1 , mapping size=14 μm×14 μm (Formula 3) Offset = WN i (Si)-WN (ref) (In formula 3, WN(ref) is the same as that in formula 2, and WN i (Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material in one pixel, which is the unit analysis area during mapping analysis.
10. In a 20 mm x 20 mm test piece, when a deviation analysis was performed based on the Raman signal of silicon at 20 different random positions, the difference between the maximum and minimum shifts defined by the following formula 3 was 5 cm -1 The negative electrode material for secondary batteries according to claim 9, wherein: Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 (Formula 3) Offset = WN i (Si)-WN (ref) (In formula 3, WN(ref) is the same as that in formula 2, and WN i (Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material in one pixel, which is the unit analysis area during mapping analysis.
11. 2. The negative electrode material for secondary batteries according to claim 1, wherein a compressive stress of 80% or more is found in stress analysis of silicon nanoparticles at 20 different random positions on a 20 mm x 20 mm test piece.
12. 2. The negative electrode material for secondary batteries according to claim 1, comprising a plurality of negative electrode material particles, and having a compositional uniformity among the particles according to the following formula 3: (Formula 4) 1.3≦UF(D) (In formula 4, UF(D) is the value obtained by dividing the average doping element composition between the negative electrode material particles by the standard deviation of the doping element composition based on the weight percent composition.)
13. 2. The negative electrode material for secondary batteries according to claim 1, wherein the silicon nanoparticles have an average diameter of 2 to 30 nm.
14. The negative electrode material for secondary batteries according to claim 1 , wherein the interface between the silicon nanoparticles and the matrix is a coherent interface.
15. 2. The negative electrode material for secondary batteries according to claim 1, wherein the doping element is at least one selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn) and bismuth (Bi).
16. The negative electrode material has an average diameter of 10 0 μm order ~ 10 1 The negative electrode material for secondary batteries according to claim 1 , which is in the form of particles on the order of μm.
17. The negative electrode material for secondary batteries according to claim 1 , further comprising a coating layer containing carbon.
18. A secondary battery comprising the negative electrode material for secondary batteries according to any one of claims 1 to 17.
Citation Information
Patent Citations
Secondary doped silicon-based negative electrode material and preparation method thereof
CN112751011A
Negative electrode active material, non-aqueous electrolyte secondary battery, and method of manufacturing them
JP2014229583A
Negative electrode material for non-aqueous electrolyte secondary battery, method for producing the same, and non-aqueous electrolyte secondary battery including the same
JP2018519648A
Negative electrode for lithium secondary battery and lithium secondary battery including the same
US20200235383A1
Anode active material, anode including the anode active material, and lithium secondary battery including the anode
KR1020150045336A
